Impact of sarcopenia on postoperative pulmonary complications after gastric cancer surgery: A retrospective cohort study - Zhang, Xiaofang; Deng, Chaoyi; Wan, Qianyi; Zhao, Rui; Han, Liping; Wang, Xiao (Frontiers in Surgery, 2023)
Background: Few studies have investigated the relationship between sarcopenia and postoperative pulmonary complications (PPCs) after gastric cancer surgery. This study aimed to explore the impact of sarcopenia on the PPCs in patients who had undergone gastric cancer surgery. Methods: We included patients who underwent a transabdominal radical gastrectomy between June 2016 and October 2020. Patients were divided into two groups according to the median prevalence rate of lumbar triplane skeletal muscle index (L3 SMI): sarcopenia group (≤37.5% percentile in male and female group) and non-sarcopenia group (>37.5% percentile in male and female group). Baseline characteristics, intraoperative and postoperative conditions, pulmonary complications, and overall complications were compared between the two groups. The primary outcome was the incidence of PPCs. The secondary outcomes were overall postoperative complications and length of stay (LOS). Results: Among the 143 patients included, 50 had sarcopenia and 93 had not. Compared with the non-sarcopenia group, the incidence of PPCs was higher in the sarcopenia group (22.0% vs. 8.6%, P=0.024). The incidence of overall postoperative complications in the sarcopenia group was higher than that in the non-sarcopenia group (36.00% vs. 20.43%, P=0.043). There was no significant difference in the LOS between the two groups. Conclusions: Our research indicates that sarcopenia, preoperative comorbidities, and longer duration of intraoperative oxygen saturation <95% were risk factors for PPCs. Sarcopenia is an independent risk factor for postoperative complications. Given that our results provided a correlation rather than causation, future prospective randomized trials are needed to confirm the relationship between sarcopenia and prognosis.